Islamic Education and the Challenges of Globalization: Strategies for Strengthening Muslim Identity - Yus Hermansyah; Badrudin; Bambang S Arifin; Rajaminsah; Elly Kusmiati; Ihwanul Muslimin (Lafadz Jaya Publisher, 2024)
Globalization has had a significant impact on various aspects of life, including Islamic education. The development of technology and the unstoppable flow of information create new challenges for efforts to strengthen Muslim identity, especially among the younger generation. This research aims to analyze the challenges faced by Islamic education in the era of globalization and identify effective strategies to strengthen Muslim identity. The research method used is a library research with data collection techniques through literature studies, and participatory observation. The results of the study show that Islamic education needs to adapt to the dynamics of globalization through the development of relevant curriculums, improvement of teacher competence, and integration of Islamic values in educational technology. In addition, the involvement of religious communities and institutions in the educational process is also an important key in strengthening Muslim identity amid the influence of globalization. This research is expected to contribute to the development of Islamic education policies that are more responsive to global challenges.